(untitled) (Eurasian Medical Research Periodical, 2023)
It is generally believed that non-alcoholic fatty liver disease (NAFLD) is a component of the metabolic syndrome and is often combined with obesity, type 2 diabetes mellitus, atherogenic dyslipidemia and its other components. However, today there is no doubt that not all obese people develop NAFLD and, on the contrary, the presence of NAFLD is possible in people with normal weight. Data on the prevalence of NAFLD without obesity in different countries are very variable – from 3 to 30%. Both exogenous (for example, excessive consumption of cholesterol and rapidly digestible fructose) and genetically determined (allelic variants of genes encoding adiponutrin, cholesterol ester transporter protein, sterol-regulating element-binding factor) are considered as risk factors for development. Diagnostic methods are not fundamentally different from those for "classical" NAFLD. Based on the analysis of the conducted studies, there are grounds to assert that lifestyle modification in the form of physical exertion and dietary restrictions contributes to the improvement of biochemical parameters and histological picture. The effectiveness of medicinal methods requires further study